Exploring the Principles of Educational Administration: The Foundation of Goal-Oriented Management (A Literature Review) - Lisniasari (Yayasan Ilomata, 2024)
This study presents a systematic review of the literature related to the principles of educational administration, with an emphasis on goal-oriented management as the main approach. The review integrates key findings from 179 documents retrieved from the Scopus database, identifying key principles such as leadership, strategic planning, decision-making, resource allocation and stakeholder engagement. The results show that these principles are crucial in aligning educational administration with institutional goals, which in turn enhances overall effectiveness and promotes continuous improvement. Although the benefits of goal-oriented management are evident, challenges such as resistance to change, limited resources and competing priorities remain obstacles. Nevertheless, opportunities for improvement remain visible, especially through technology integration, professional development, and collaborative partnerships. The findings offer valuable insights for education administrators and policymakers who want to implement goal-oriented management practices to drive better educational outcomes.